2021
DOI: 10.21037/gs-21-417
|View full text |Cite
|
Sign up to set email alerts
|

A clinical observation of stage I implant breast reconstruction for mass-like granulomatous lobular mastitis

Abstract: Background: Granulomatous lobular mastitis (GLM) is a chronic benign inflammatory breast disease, and mainly mass-like granulomatous lobular mastitis (MGLM) clinically. There are few reports on applications of stage I implant breast reconstruction in GLM. This observational study was conducted to evaluate the safety and efficacy of stage I implant breast reconstruction in the treatment of MGLM. Methods: Patients suffering from MGLM who visited at hospital from April 2019 to June 2020 were selected and graded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Otherwise, prolonged excision may leave a large tissue defect that is difficult to close, resulting in a negative cosmetic outcome [ 27 ]. As a result, some authors recommend stage I prosthesis implantation for patients with IGM after conservative treatment for definitive efficacy and high patient satisfaction [ 16 ], or delayed breast reconstruction to monitor surgical recurrence [ 28 ]. We advocate wide excision and reconstruction with simultaneous plastic and reconstructive breast surgery techniques for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, prolonged excision may leave a large tissue defect that is difficult to close, resulting in a negative cosmetic outcome [ 27 ]. As a result, some authors recommend stage I prosthesis implantation for patients with IGM after conservative treatment for definitive efficacy and high patient satisfaction [ 16 ], or delayed breast reconstruction to monitor surgical recurrence [ 28 ]. We advocate wide excision and reconstruction with simultaneous plastic and reconstructive breast surgery techniques for patients.…”
Section: Discussionmentioning
confidence: 99%
“…While these techniques allow wide surgical excisions in patients with breast cancer, they also aim to protect the breast. Similarly, many authors have used these new techniques derived from plastic surgery techniques to ensure wide surgical excisions in the surgical management of IGM [ 7 8 14 15 16 ]. Although the term ‘oncoplastic’ in conjunction with the techniques used in the surgical treatment of benign breast disease has created confusion of terms, no author has proposed a new definition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because GLM usually presents as a fairly large breast mass, surgical resection often leads to poor plastic results and severe breast malformations. In order to improve this result, Zhang et al (119) have conducted clinical study on stage I implant breast reconstruction after surgical resection of lesions. The results showed that after primary prosthesis implantation, patients had higher breast shape satisfaction (88.9%) and lower postoperative infection rate (5.6%), suggesting that this method can be used as an optional method for breast reconstruction in patients after larger lesion resection.…”
Section: Surgerymentioning
confidence: 99%